Development of a Solar Fish Dryer (Biological Sciences - PJSIR, 2009)
The solar fish dryer developed for particular conditions of Bishop Village, Lagos, Nigeria absorbs sunlight with a flat plate collector for its air heater. Mirrors are appended to one of the collector sides to enhance collection of solar radiations. The dryer is a passive type, tailored to solve the energy needs of the people of the area. On days of high irradiance, temperature within the solar fish dryer can be as high as 80°C with relative humidity around 10%.